Techniques for optimizing mobile app performance in terms of speed, responsiveness, and battery consumption - Syed Umar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Optimizing mobile app performance is critical for enhancing user experience, reducing battery consumption, and ensuring seamless responsiveness. This study explores advanced techniques for improving app speed, responsiveness, and energy efficiency across various mobile platforms. Key strategies include employing efficient code practices, leveraging asynchronous processing, and minimizing memory overhead. Adaptive data handling through caching, compression, and optimized API usage is discussed to reduce latency. Additionally, strategies for reducing battery drain, such as power-efficient resource management, reducing background activity, and leveraging platform-specific optimization tools, are presented. The paper also investigates real-time monitoring and profiling techniques for detecting performance bottlenecks. By integrating these methods, developers can deliver high-performance apps that meet user expectations while optimizing resource utilization.